The Dynamic of Religious Life: A Study of Conflict and Integration of Ahmadiyah in Garut, Tasikmalaya and Kuningan, West Java - Nurdin, Ahmad Ali; Jamaludin, Adon Nasrullah; Supriatna, Encup; Kustana, Kustana (Komunitas, 2019)
The conflict does not automatically lead to disintegration. Sociologist like Georg Simmel and Lewis Coser reinforce this assumption. Conflict can also function to strengthen social groups and restore social integration. Conflict and integration (harmony) like two sides of a coin, different but still one. This paper supports the assumption above. After the conflict between the community and Ahmadiyah’s followers in the three Regencies (Garut, Tasikmalaya and Kuningan), they live in harmony (integration). This fact in line with the argument of Georg Simmel and Lewis Coser. This study showed that the conflicts occurred in three regencies (Garut, Tasikmalaya and Kuningan), did not make the Ahmadiyah adherents disintegrated and crumbled. But on the contrary, Ahmadiyah followers increasingly integrated, solid and live co-exist with the non-Ahmadiyah community and live harmoniously.